Modyfikacje systemów gwarantowania depozytów bankowych w konsekwencji globalnego kryzysu finansowego - Gospodarowicz, Marcin (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article attempts to review the changes in the deposit guarantee systemresulting from the global financial crisis. There were two stages of regulatorychanges. One in the initial years of the crisis (2008-2009) when the changes werereactive in nature and focused in particular on raising the guarantee limits andrelief operations. As can be seen from the example of regulatory action in theEuropean Union, the present stage of changes in the deposit guarantee system ischaracterized by a systemic approach which attempts to position anew depositguarantees in the context of the financial safety net, particularly against thedevelopment of resolution procedures.